The Influence Of Management Accounting On Sales Management In The Tanah Abang Family Clothing Store - Rizky Maharani Rustam; Wulandari Pryangan; Burhanuddin; Gjospink Putra Umar Sakka; Tuti Dharmawati (Jurusan Akuntansi FEB UHO, 2023)
The purpose of this research is to analyze the influence of management accounting at the Tanah Abang Clothing Family Store. This research uses management accounting system theory in the form of knowledge that contains management accounting information (finance, production, marketing, personnel and so on) provided to assist leaders in making decisions about the company's future and in controlling the implementation that has been made. The research method uses a qualitative research method which is a research method with a descriptive approach where in its application it seeks meaning from the data obtained based on the results of the research carried out. The data collected in this research includes two types, namely primary data and secondary data. The data collection techniques were carried out through: interviews; carried out on workers at the Tanah Abang Family Clothing Shop The results of this research show that the accounting information system for management of store turnover or income data has an influence on decision making regarding sales of the Tanah Abang Family Clothing Store with changes in sales strategy. It can be concluded that the sales strategy using conventional digital payment transactions changing to digital transactions has had a positive impact on the shop. Thus, the decision to make changes to the strategy based on management accounting information, income turnover data in January to March until june to august had a positive impact on creating a better strategy for the sales of the Tanah Abang Family Clothing Store.